ADVANTAGES OF BROAD SPECTRUM ANTIEPILEPTIC DRUGS IN TREATMENT OF EPILEPSY - K. V. Voronkova; G. S. Golosnaya; I. D. Lemeshko; A. S. Petrukhin (Эпилепсия и пароксизмальные состояния, 2017)
Pharmacotherapy of epilepsy requires deep knowledge  of anti-epileptic drugs (AEDs), including the following issues: spectrum of therapeutic efficacy and therapeutic strength, adverse effects (especially severe and life-threatening adverse reactions); specific features of pharmacokinetics,  pharmacodynamics, and drug interactions; titration rate, the need for laboratory tests  during treatment,  pharmacoeconomic components.  The main properties  of antiepileptic drugs  are defined by their mechanisms of action. Today, particular attention is paid to the drugs with broad spectrum  activity, which give an ability to use them in patients with so-called undifferentiated epilepsies. In this article, the authors describe their own experience in optimization of antiepileptic therapy in a group of 141 patients with various forms of epilepsy. This new optimized  strategy implies inclusion of modern  broad spectrum  AEDs in treatment  schemes along with the reduction  in use  of narrow spectrum  drugs.  Moreover, polytherapy  was  used  in most  of the cases  after treatment regimen correction. All the measures  allowed to achieve remission  in about half of the patients with epilepsy earlier considered as incurable.